Imam AL-Junaid Al-Baghdadi : pemimpin kaum sufi / Ali Hassan Abdel-Kader; penerjemah, Irfan Zakki Ibrahim; penyunting, Zulkarnaen Ishak - Abdel-Kader, Ali Hassan, ; Irfan Zakki Ibrahim ; Zulkarnaen Ishak (Diva Press, 2018)
392 halaman ; 20 cm